Persistent Ureteric Dilatation due to Pelvic Actinomycosis Presenting as Pelvic Inflammatory Disease. (10th July 2011) - Khafagy, Richard; Jundi, Omar; Rogawski, Karol; Namasiviyam, Siva
Abstract : Actinomyces is a Gram-positive, filamentous bacterium that normally colonizes mucosal areas. Pelvic actinomycosis is a chronic granulomatous disease caused by Actinomyces israelii that frequently mimics ovarian tumors during presentation. It is diagnosed after surgery in most of the cases. Intravenous penicillin is the most preferred therapeutic agent, and it requires hospitalization up to one month. Pelvic actinomycosis is a rare cause of ureteric obstruction and renal failure. The final diagnosis is usually difficult and often apparent only after histological examination of an operative specimen. The present case led us to consider the etiology and clinical findings and to review the management of reported cases involving ureteric obstruction.